Faktor yang Mempengaruhi Kejadian Picky Eating Pada Anak - Rizki Arisandi (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Picky eating is included in the feeding difficulties spectrum, where the children refuse newly introduced food, or only want to eat a certain type of food. Picky eating can impact the nutritional status of the children because a picky eater tends to have a lower nutrition intake originated from the food they refuse, especially micronutrients such as magnesium (Mg), iron (Fe), dan the other micronutrients. The factors influencing the picky eating occurrence in children are genetic factors, prenatal factors, postnatal food intake, and family environment.